Prevalence of Sarcopenia in Liver Cirrhosis Patients and Determinants of Survival in Cirrhotic Population: A Prospective Cohort Study - Bini Balakrishnan; B Vijayalakshmi; KT Shenoy; KB Leena; P Jayakumar; JK Mukkadan (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Chronic liver diseases are the leading cause of mortality and are associated with a significant reduction in health-related quality of life, as well as being a major complication in cirrhosis. There is a high risk of reduced muscle mass, muscle strength, or function, known as sarcopenia, in patients with liver cirrhosis. Sarcopenia is a major determinant of survival in cirrhosis patients, along with the Child-Turcotte Pugh (CTP) score and the Model for End-stage Liver Disease (MELD) scores. Aim: To study the prevalence of sarcopenia in patients with liver cirrhosis by assessing skeletal muscle mass using the third lumbar level Skeletal Muscle Index (SMI) through Computed Tomography (CT) and to determine the survival analysis of the cohort using a Cox regression model. Materials and Methods: The present study was a prospective cohort study conducted in the Department of Gastroenterology and Hepatology at Sree Gokulam Medical College and Research Foundation in Thiruvananthapuram, Kerala, India South India, from October 2018 to October 2022. A total of 209 patients with cirrhosis were evaluated. Liver biochemical parameters, CTP score, and the MELD score were studied. Age, gender, and aetiology were noted. All subjects were assessed for sarcopenia using CT at the third lumbar vertebrae level SMI, and all subjects were followed up every six months for survival. Survival curves and survival probability were evaluated for all the subjects recruited in the present study. Cumulative survival rates were estimated by the Kaplan-Meier method for sarcopenia, CTP score, and the MELD scores after categorisation into the aetiology of cirrhosis, and the groups were compared using the Log-rank test. Independent factors associated with mortality were identified using Cox proportional hazards models. A p-value <0.05 was considered statistically significant. Results: The mean age±Standard Deviation of the subjects was 58.24±9.9 years. Among the subjects, males accounted for 161 (77%), while 48 (23%) were females. In subjects with sarcopenia (n=77), the survival rate was 53 (68.8%), and in subjects without sarcopenia (n=132), the survival rate was significantly higher at 110 (83.3%) with a p-value <0.05 (p=0.027). Univariate Cox regression analysis indicated that sarcopenia was a statistically significant predictor of survival. The mortality risk was higher in individuals with sarcopenia, with a Hazard Ratio (HR) of 1.9 and a 95% Confidence Interval (CI) ranging from 1.1-1.4. In the Cox regression model, CTP class B/C had a 2.4 times higher risk for mortality than CTP class A (p<0.05). Individuals with sarcopenia had a 1.76 times higher risk of mortality compared to those without (HR=1.765, 95% CI: 0.983-3.17) in the multivariate Cox regression analysis. Aetiology and CTP class scores were independently associated with mortality (p<0.05) after adjusting for multiple prognostic factors in the multivariate Cox regression analysis. Conclusion: Univariate Cox regression analysis indicated that sarcopenia was a statistically significant predictor of survival, with a higher mortality risk in individuals with sarcopenia. The multivariate Cox regression model for survival concluded that CTP class B/C posed a higher risk for mortality compared to CTP class A.